TRANSLATION SHIFT OF VERB AND SENTENCE STYLE FROM ENGLISH INTO BAHASA INDONESIAN - Diah Supatmiwati (International Conference on Education and Language (ICEL), 2016)
This paper explores translation shift of verb and sentence style from English into Bahasa Indonesian. The main problem is to discuss what kinds of shift found in Source Text (ST) and the realization in Target Text (TT). Shift is needed in translating and there also some factors play important role in the process of transferring. This is qualitative research which is base on text analysis. A descriptive analysis is conducted to compare both analyzed texts. The method goes thru 3 main stages starting from data classification, analysis and discussion. The theories applied in this study are: translation equivalence suggested by Cadford, and focuses on level shifts, where the SL item at one linguistic level (e.g. grammar) has a TL equivalent at a different level (e.g. lexis) and to investigate what decisions are made during the translation, and what is directing those decisions. A thorough analysis of selected texts will connect the differences in translational behavior to the norms that govern this behavior. The finding suggests that there some shifts in translating English to Bahasa Indonesia. In Bahasa Indonesia passive is more common style in writing report or scientific article.